Improving The Quality of Life and Resilience of The Elderly with Emotion Regulation Exercises - Rakhmawati, Indriana; Nurhalimah, Nurhalimah; Utami, Tantri Widyarti (Jurnal Keperawatan, 2024)
The quality of life of the elderly will increase if they have psychological resilience to stress. Emotional regulation is the ability of older people to manage emotional responses in dealing with various stressors in life which will increase psychological resilience (the ability to overcome problems/stress) and quality of life. Objective. This research was conducted to find out whether emotional regulation interventions for the elderly have an effect on their quality of life and psychological resilience. This type of research is quantitative with a one group pretest-posttest design. The sample consisted of 36 elderly people who were selected using the purposive sampling method. The research process begins with administrative permits and questionnaire testing. Next, respondents were given emotional regulation training (4 meetings) and their resilience and quality of life were measured before and after the training. The instruments used to measure it are the Resilience Questionnaire (RSOA) and the Quality of Life Questionnaire (WHOQOL-Bref). Data were analyzed univariately using frequency and mean methods, bivariately using Spearmann rho correlation. The research results show that emotional regulation training can improve the resilience and quality of life of the elderly.